The Effect of Trellis Systems on the Performance of Vitis vinif era L. cvs. Sultanina and Chenel in the Lower Orange River Region - Swanepoel, J.J.; Hunter, J.J.; Archer, E. (South African Journal of Enology and Viticulture, 2017)
The effect of six trellis systems on the reproductive and vegetative performance of Sultanina and Chene), grown in the lower Orange River region of South Africa, was investigated. Larger trellis systems significantly increased the yield of both cultivars, and the photosynthetic activities of the leaves at veraison as well as the canopy light environment tended to be higher for these systems. The higher yields recorded for Sultanina were attributed to improved budding percentages, which were caused by improved light environments at the basal ’buds. The improved yield obtained for Chene! however, was due to higher bunch masses, which were most likely caused by the higher photosynthetic activities of the leaves.